Instruments for assessing the quality of life of elderly people with alzheimer’s: integrative literature review - França, Alex Bacadini (2016)
The use of instruments to evaluate the quality of life of elderly people with Alzheimer’s is of great use for implementing adequate care for this population. The objective of this study is to seek in the literature evidence of the validity of the instruments that evaluate the quality of life of elderly people with Alzheimer’s, answered by the patients themselves. It is an integrative review of the literature. The search in the databases was performed in PubMed, Lilacs, and CINAHL. Ten articles were selected for comprehensive analysis. This review allowed a main evaluation tool to be identified (QoL-AD), validated for the different populations, as well as the proposal of two new instruments (DQI and BASQID). The analysis of the properties of validity and internal consistency (reliability) of the instruments found them to be satisfactory. It also reinforced the notion pointed out by the authors regarding the dependence among the dimensions of the quality of life of the elderly and Alzheimer’s disease.